2001
DOI: 10.1002/ijc.1639
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the INK4a/ARF locus and p53 in sporadic extrahepatic bile duct cancers and bile tract cancer cell lines

Abstract: The tumor-suppressor genes p14(ARF), p16(INK4a) and Tp53 are commonly inactivated in many tumors. We investigated their role in the pathogenesis of 9 bile tract cancer cell lines and 21 primary sporadic extrahepatic bile duct carcinomas. p53 and p16 protein expression was examined by Western blot analysis and immunohistochemistry. Mutation screening of p53 was done by SSCP and direct sequencing. Inactivating mechanisms of p14 and p16 were addressed by screening for mutations, homozygous deletions, chromosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 50 publications
2
37
0
8
Order By: Relevance
“…Loss of p16 expression is correlated with homozygous deletion of the p16 gene in gallbladder cancer and other malignancies. Eight of nine biliary tract cell lines with homozygous deletion of the p16 gene showed loss of p16 expression, as reported by Caca et al [26] . In our series, loss of p16 expression correlated with homozygous deletion of the p16 gene in nine of 13 tumors.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Loss of p16 expression is correlated with homozygous deletion of the p16 gene in gallbladder cancer and other malignancies. Eight of nine biliary tract cell lines with homozygous deletion of the p16 gene showed loss of p16 expression, as reported by Caca et al [26] . In our series, loss of p16 expression correlated with homozygous deletion of the p16 gene in nine of 13 tumors.…”
Section: Discussionsupporting
confidence: 75%
“…Ku et al have reported that homozygous deletion of the p16 gene was found in three of six biliary tract cell lines, but no p16 mutation was found in the remaining three biliary tract cell lines, which did not show homozygous deletion. Caca et al [26] have reported that p16 mutations were not found in three biliary tract cell lines and 21 biliary tract cancers, which did not show homozygous deletion of the p16 gene. In the present study, a p16 mutation was not found in any of the cases analyzed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Upon ZOL treatment a dose-dependent decrease in the level of p27 inhibitor was observed in both cell lines, more evident in EGI-1 cells. The p16 INK4A , which shares with pRb and p27 a regulatory role at G1/S checkpoint, is frequently mutated or deleted in a wide variety of tumors, in particular in bile duct cancers, and not expressed in the cholangiocarcinoma cell lines used in this work [31,32]. In several human malignancies, the loss, mutation or silencing of the gene encoding the CDK4 inhibitor p16 INK4a hyperactivates the kinase activity of CDK4 [33][34][35].…”
Section: Expression Of Putative Phase Markers and Cell Cycle Regulatorsmentioning
confidence: 95%
“…Para los adenocarcinomas pancreáticos de los cuales el 98% de los tumores demuestra ausencia del p16, 48% de alteraciones genéticas en el gen CDKN2A son de lesiones homocigotas y 34% están asociadas con una pérdida de heterocigocidad (LOH), mientras el resto está relacionada con un silenciamiento mediante metilación de las áreas promotoras 25 . Más aún la pérdida del cromosoma 9p21 es común en los carcinomas del tracto de vía biliar y de la vesícula biliar 26,27 . En nuestro estudio encontramos que el 11% de los adenocarcinomas exhibían desbalance alélico en uno de los microsatélites que flanquean la región del cromosoma 9p en el cual el gen CDKN2A está localizado (Tabla 1).…”
Section: A R T í C U L O D E I N V E S T I G a C I ó Nunclassified